Warientalism, or the Carrier of Firewood - Mohamed Salah Eddine Madiou (Arab Studies Quarterly, 2021)
The world, under Donald Trump's presidency, inaugurated a “new” way of dealing with international affairs, one abrupt and unapologetic, making the world into a world of warcraft . Trump came up with a “might is right” rule as a “solution” that proved, because official , to be of such a strong force of influence and legitimization it gained inter/intra national traction, impacting the behavior of both the ruling and “less ruling” circles. In this theoretical essay, I locate the necessity to introduce a new concept, Warientalism, that refers to a discourse of power befitting today's “politics,” and some “politics” of bygone days. It proposes to conceptually define Warientalism, and critically examine its discourse.